PEMBENTUKAN BISNIS YANG BERETIKA MELALUI EDUKASI ETIKA BISNIS UNTUK PENGUSAHA UMKM THRIFT SHOP KARANG SUKUN - Muhammad Taufik; L. Jatmiko Jati; Harfina Yulistia (CV SWA Anugerah, 2023)
Thrift Shop Karang Sukun is well known as Pasar Rombengan. It is one of the Micro, Small, and Medium Enterprises (MSMEs) that operates in the fashion industry specifically selling used clothes. Business ethics education for MSMEs has an important role in forming honest, fair and responsible behavior in running a business. This research aims to promote ethical business through business ethics education for Karang Sukun Thrift Shop MSME entrepreneurs. And this research also observed changes in business behavior after business ethics education was provided. This research shows a significant increase in knowledge and understanding of business ethics among second-hand clothing MSME owners after receiving education. Apart from that, business ethics education can influence business behavior in the used clothing MSME environment. It is hoped that this research will be useful for MSME entrepreneurs, especially Karang Sukun thrift shop.